The exchange of tax information and its impact on fundamental rights (Revista do Tribunal Regional Federal da 3ª Região, 2022)
In a globalized world, where tax relations are becoming increasingly complex, the need for greater international cooperation arises to States, in order to prevent double taxation and double non-taxation. This study aims to show that the institute of information exchange is an option to this cooperation, however, its use, by reflecting directly on fundamental rights, must be carefully analyzed and considered.
Keywords: Globalization; international cooperation; double taxation; double non-taxation; information exchange; fundamental rights